Is the intrinsic value of macroeconomic news announcements related to their asset price impact? - Thomas Gilbert; Chiara Scotti; Georg Strasser; Clara Vega (European Central Bank (ECB), 2016)
The literature documents a heterogeneous asset price response to macroeconomic news announcements: Some announcements have a strong impact on asset prices and others do not. In order to explain these differences, we estimate a novel measure of the intrinsic value of a macroeconomic announcement, which we define as the announcement's ability to nowcast GDP growth, inflation, and the Federal Funds Target Rate. Using the same nowcasting framework, we then decompose this intrinsic value into the announcement's characteristics: its relation to fundamentals, timing, and revision noise. We find that in the 1998–2013 period, a significant fraction of the variation in the announcements' price impact on the Treasury bond futures market can be explained by differences in intrinsic value. Furthermore, our novel measure of timing explains significantly more of this variation than the announcements' relation to fundamentals, reporting lag (which previous studies have used as a measure of timing), or revision noise.
Keywords: G14; E44; 330; coordination role of public information; learning; macroeconomic announcements; macroeconomic forecasting; price discovery